Does 18F-FDG PET/CT change the surgical management of potentially resectable colorectal liver metastases?. (March 2022) - Jonsson, Josefin; Hemmingsson, Oskar; Strengbom, Rebecca; Axelsson, Jan; Riklund, Katrine; Nyström, Hanna
Purpose: Resectability assessment of patients with colorectal liver metastases is based on computed tomography and liver magnetic resonance imaging. Addition of fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography has been recommended, but the impact of the added information remains unclear. The primary aim of this study was to determine how preoperative positron emission tomography/computed tomography changed management in patients with potentially resectable colorectal liver metastases. The secondary aim was to investigate whether findings on positron emission tomography/computed tomography correlated to metastatic disease in cases with extended surgery and influenced oncological outcomes. Methods: A retrospective observational study of the impact of adding positron emission tomography/computed tomography to conventional imaging in the surgical decision-making of colorectal liver metastases. All patients with colorectal liver metastases diagnosed by conventional imaging were included and assessed by a multidisciplinary team conference at Umeå University Hospital between June 2013 and December 2017. Eligibility criteria were all patients with potentially resectable colorectal liver metastases. Patients who underwent preoperative positron emission tomography/computed tomography in addition to conventional radiology were compared with those who underwent conventional imaging only. Results: 151/220 patients underwent preoperative positron emission tomography/computed tomography. Findings on positron emission tomography/computed tomography changed the management in 10.6% of the patients. Eight patients were excluded from surgery after detection by positron emission tomography/computed tomography of extrahepatic disease. Eight patients underwent more extended surgery than initially planned due to positron emission tomography/computed tomography. Five of these positron emission tomography-positive resected sites were verified by pathology as metastatic disease. No difference in overall survival was seen following surgical resection in patients with and without a preoperative positron emission tomography/computed tomography. Conclusions: Preoperative positron emission tomography/computed tomography resulted in a changed surgical management in 10.6% of cases in a selected cohort.